Analisis Pelaksanaan Pelayanan Penderita Hipertensi dan Diabetes Mellitus dalam Peningkatan Capaian Standar Pelayanan Minimal - Ernawati, Tuty; Siswati, Sri; Anshari, Luthfil Hadi (Jurnal Kesehatan Komunitas, 2025)
Indonesia is currently facing a double burden of disease, comprising both communicable and non-communicable diseases (NCDs), each of which has a significant impact on public health and national economic growth. NCDs such as hypertension and diabetes mellitus have become leading causes of morbidity and mortality, requiring serious attention.To ensure the quality of healthcare services, the government has established standards through Minister of Health Regulation No. 6 of 2024 concerning Technical Standards for Fulfilling the Quality of Basic Services under the Minimum Service Standards (SPM) in the health sector.This study aims to analyze the implementation of healthcare services for patients with hypertension and diabetes mellitus in an effort to improve SPM achievement at Alahan Panjang Public Health Center (Puskesmas), Solok Regency.The research employed a mixed-methods approach, combining quantitative and qualitative methods to gain a more comprehensive understanding.The results showed that 44.6% of patients had a low level of knowledge about their disease, while 55.4% had a high level of knowledge. The Puskesmas has implemented an NCD program based on Minister of Health Regulation No. 71 of 2015 and has its own Standard Operating Procedures (SOPs). The performance of healthcare personnel was generally adequate, but there were challenges due to scheduling conflicts with integrated Posyandu (community health post) activities. Budget constraints from the district health office also affected program funding. In addition, the availability of medical equipment, such as blood pressure monitors, remains limited. The implementation of integrated Posyandu services alongside NCD programs and other life cycle-based activities has been initiated, but these efforts do not always run optimally due to limited human resources and infrastructure. These findings highlight the need to strengthen support for NCD services to achieve the 100% SPM target.